Relationship between Porosity-Ultrasonic Pulse Velocity and Water Absorption of Concrete Containing Plastic and Rubber Waste by Full Factor Desing - Belmouhoub Ameur; Abdelouahed Assia (Selected Scientific Papers: Journal of Civil Engineering)
Utilizing waste plastic and rubber in civil engineering is one of the most environmentally friendly and economically advantageous options. In this work, the aim was to study the relationship between porosity, ultrasonic pulse velocity, and water absorption using waste plastic and rubber in ordinary concrete and analyze the results with a program called JMP, where cement was replaced with rubber as a mass substitute in proportions of 2% and 4% and sand was replaced with plastic as a mass substitute in proportions of 2%, 4%, and 6%. The tests used were ultrasonic speed at 28 days, porosity, water absorption by total immersion, and sorptivity. The findings reveal that as the amount of rubber and plastic increases, the speed of ultrasonic decreases. Additionally, higher amounts of rubber and plastic lead to increased porosity, water absorption by total immersion, and sorptivity. The speed of ultrasonic pulses varies between 4065.04 m/s and 3838.90 m/s, porosity levels range from 11.63% to 13.44%, water absorption by total immersion falls between 5.40% and 6.16%, and sorptivity ranges from 9.93 g/m2 to 13.99 g/m2. Furthermore, the addition of rubber and plastic waste causes large voids and cracks to form inside the concrete structure. These voids and cracks can increase the porosity of the concrete, which raises the rate of water absorption and lowers the ultrasonic pulse velocity, according to scanning electron microscopy (SEM) data. After assessing the data, it was determined that the numerical simulations for various factors such as ultrasonic pulse velocity, porosity, water absorption by total immersion, and water absorption by capillary exhibited strong correlation, with calculated coefficients R² near 1.